Continuous magma mixing and cumulate separation in the High Tatra Mountains open system granitoid intrusion, Western Carpathians (Poland/Slovakia): a textural and geochemical study - Crowley, Quentin (My University, 2019)
In this study the formation of the polygenetic High Tatra granitoid magma is discussed. Felsic and mafic magma mixing and mingling processes occurred in all magma batches composing the pluton, but were developed to different extents. The magma mixing and mingling processes are documented by the typical textural assemblages, which include: mafic microgranular enclaves (MME), mafic clots, felsic clots, quartz-plagioclase-titanite ocelli, biotite-quartz ocelli, poikilitic plagioclase crystals, chemically zoned K-feldspar phenocrysts with inclusion zones and calcic spikes in zoned plagioclase. Geochemical modelling indicates the predominance of the felsic component in subsequent magma batches, however, the amount of mafic component increased with time. Magma mixing is considered to be a first-order magmatic process, causing the magma diversification. Influx of mafic, low viscosity and volatile-rich magma stimulated the formation of cumulates, both mafic and alkali feldspar-dominated types. The cumulate formation and the squeezing of remnant melt by filter pressing points to fractional crystallization acting as a second-order magmatic process. Mantle origin of the admixed magma input is suggested on the basis of geochemical and Rb-Sr, Sm-Nd and Pb-Pb isotopic data.
PUBLISHED
Keywords: Tatra granitoids; Magma mixing; Cumulate formation; Smart & Sustainable Planet; MAGMATIC PROCESSES; magma mixing